Dispersal dynamics of juvenile Secretarybirds Sagittarius serpentarius in southern Africa. (4th May 2019) - Whitecross, Melissa A; Retief, Ernst F; Smit-Robinson, Hanneline A
Abstract : Knowledge of the dispersal behaviour of southern Africa's juvenile Secretarybirds Sagittarius serpentarius was previously limited to a small number of ring recoveries ( n = 4) in South Africa. From 2012 to 2015, 10 GSM-GPS solar trackers were fitted to juvenile Secretarybirds, aged approximately eight weeks, on their nests. The birds spent an average of 91.30 ± 8.80 d in their natal territories, which had a mean home range size (kernel density estimate 90%) of 1.21 ± 0.34 km 2 . As they aged, their exploratory movements around the nest expanded exponentially. During this period, exploratory activity peaked between 09:00 and 12:00. They showed high variability in maximum distance travelled from the nest and timing of dispersal from their natal territories. Most of the birds ( n = 7) dispersed >150 km from their nests before returning to their natal region, suggesting the existence of natal philopatry in this species. The age of first breeding for a male Secretarybird was also confirmed during this study. The wide-ranging behaviour of juvenile Secretarybirds exposes them to a diverse range of threats, and a better understanding of their movements will aid the development of appropriate conservation strategies for this terrestrial raptor.